Digital Transformation of Enterprise Learning: A Case Study of China Telecom - Jiaqi He; Yuanyuan Gong; Yingying Hu (Adult Education Research Conference, 2023)
This study aimed to explore the digital transformation of enterprise learning. Through the case study of China Telecom, we studied how it transformed and its transformation dimensions.
Keywords: digital transformatio; enterprise learning; China Telecom